Sub-lethal effects of acetamiprid on the gills of the bleak Alburnus alburnus: histopathological and molecular alterations - R. Agaguena; N. Zaidi; E. Brunelli; A. Hamdani; R. Macirella (The European Zoological Journal)
The widespread and uncontrolled application of neonicotinoid pesticides represents a major threat to freshwater ecosystems, especially those near agricultural lands and farms. Here, we determined for the first time the mean lethal concentration (LC50–96 h) of acetamiprid on bleak Alburnus alburnus juveniles and investigated the effect on gills of two environmentally relevant concentrations after short-term exposure (96 h). After defining the LC50 value (34.546 mg/L), we evaluated the effects of two low concentrations (150 and 300 µg/L) through a histological examination and molecular evaluation of Na+/K+-ATPase expression in gills. No morphological alterations were observed in the control group. Severe structural modifications were observed in samples exposed to both tested concentrations, including hyperplasia and hypertrophy of chloride cells, epithelial detachment and aneurysm formation, which are recognised as a common and early response of freshwater gills to chemical insults. Exposure to the highest tested concentration induced more severe damage, with the appearance of necrotic pavement cells and degeneration of pillar cells. Na+/K+-ATPase downregulation was observed following the exposure to both tested concentrations. Our results highlight the importance of expanding the panel of ecotoxicological tests required to approve agrochemical compounds and using different diagnostic tools for an in-depth examination of xenobiotic toxicity.